Differential activity of wheat antioxidant defense system and alterations in the accumulation of osmolytes at different developmental stages as influenced by marigold (Tagetes erecta L.) leachates - Mir, Rayees Ahmad; Argal, Surendra; Ahanger, Mohammad Abass; Jatav, Keshav Singh; Agarwal, Rajiv Mohan (Frontiers in Plant Science, 2022)
Abstract: Experiments were conducted to evaluate the effectivity of Tagetes erecta L. leachates on various growth, physiological and biochemical parameters of wheat at different stages of growth. Results suggested that Triticum aestivum L. seedlings/plants when exposed to higher concentration of marigold leachates (10%, 20% and 30% w/v of fresh parts and 5% and 10% w/v of dry parts) exhibited enhanced lipid peroxidation along with increase in the activity of protease and phenylalanine ammonia lyase. Treatment of higher concentration of leachates of fresh (30% w/v) and dry (10% w/v) T. erecta up-regulated the activity of superoxide dismutase, catalase, ascorbate peroxidase, guaiacol peroxidase, glutathione S-transferase, glutathione reductase and also increased the non-enzymatic components of antioxidant defence such as, glutathione, ascorbic acid, total phenols along with osmotic constituents comprising free proline, free sugars and free aminoacids in wheat. Growth and yield attributes of wheat exhibited slight increase at treatments of lower concentrations (1% w/v) of dry leachates whereas, decrease was recorded at higher concentrations (10% w/v). In general, treatments of flower leachates (higher concentrations) showed greater influence as compared to those of leaf leachates. Identification and understanding the mechanism of working of allelochemicals in these leachates may pave way for further experimentation on Tagetes erecta L crop while it is cultivated and decomposed in the field.